Causal model and guidelines for enhancing teacher engagement and teacher performance in language schools in Thailand - Jitrlada Lojanatorn; Poschanan Niramitchainont; Sovaritthon Chansaengsee (Environment and Social Psychology, 2025)
The purpose of this study was to examine a causal model of teacher engagement and performance, and to develop guidelines to enhance teacher development in language schools in Thailand. A mixed-methods approach was employed, combining quantitative and qualitative data. The quantitative phase involved a survey of 517 teachers selected through simple random sampling, while the qualitative phase included focus group discussions with 12 key informants chosen through purposive and convenience sampling. Data were analyzed using descriptive statistics, structural equation modeling, and content validation. The findings revealed that grit, quality of work life, and teacher engagement significantly predicted teacher performance, whereas workplace learning showed no direct effect. Among these, teacher engagement emerged as the strongest predictor of teacher performance. Based on these results, ten practical guidelines were proposed to strengthen teacher performance and support sustainable school improvement. These included initiatives to provide platforms for showcasing teacher skills, establish fair workload distribution, enhance mentoring and feedback systems, revise compensation methods, improve teaching resources, and incorporate teacher ability assessments into recruitment processes. Collectively, these measures are expected to promote teacher motivation, resilience, and effectiveness, thereby contributing to the overall quality of language education in Thailand.